ROMSPath v1.0: offline particle tracking for the Regional Ocean Modeling System (ROMS) - E. J. Hunter; H. L. Fuchs; J. L. Wilkin; G. P. Gerbi; R. J. Chant; J. C. Garwood (Geoscientific Model Development, 2022)
Offline particle tracking (OPT) is a widely used tool for the analysis of data in oceanographic research. Given the output of a hydrodynamic model, OPT can provide answers to a wide variety of research questions involving fluid kinematics, zooplankton transport, the dispersion of pollutants, and the fate of chemical tracers, among others. In this paper, we introduce ROMSPath, an OPT model designed to complement the Regional Ocean Modeling System (ROMS). Based on the Lagrangian TRANSport (LTRANS) model (North et al., 2008), ROMSPath is written in Fortran 90 and provides advancements in functionality and efficiency compared to LTRANS. First, ROMSPath calculates particle trajectories using the ROMS native grid, which provides advantages in interpolation, masking, and boundary interaction while improving accuracy. Second, ROMSPath enables simulated particles to pass between nested ROMS grids, which is an increasingly popular scheme to simulate the ocean over multiple scales. Third, the ROMSPath vertical turbulence module enables the turbulent (diffusion) time step and advection time step to be specified separately, adding flexibility and improving computational efficiency. Lastly, ROMSPath includes new infrastructure which enables inputting of auxiliary parameters for added functionality. In particular, Stokes drift can be input and added to particle advection. Here we describe the details of these updates and performance improvements.